Influence of Social Media Marketing on Consumer’s Buying Decision of Fashion Products in Kathmandu (Southwestern Research Journal, 2024)
The objective of study to examine the relationships between key factors—Informativeness, E-WOM, Ad Perceived Value, Entertainment, and Consumer Buying Decisions. It focuses on how these factors influence consumer choices when buying fashion products online. The research targeted individuals who have used social media platforms for online shopping in the Kathmandu Valley, with a sample size of 282 participants. Convenience sampling was used to select participants. The study used correlational and causal-comparative research designs, gathering primary data through a survey questionnaire. Hypothesis testing and regression analysis were applied to understand the relationships between the factors influencing consumer buying decisions. The regression model revealed a moderate positive correlation between the predictor variables and consumer buying decisions, showing that these factors together explained a significant portion of the variation in buying decisions. The results indicate that Perceived Value of Ads and Entertainment have a moderate positive effect on consumer buying decisions. Participants who found ads valuable and entertaining were more likely to make a purchase. E-WOM and Informativeness also showed statistically significant, but slightly weaker, correlations with buying decisions. These findings emphasize the importance of creating advertisements that are both valuable and entertaining, providing useful insights for marketing strategies aimed at influencing consumer behavior.